2021
DOI: 10.3390/antiox10121884
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Is Involved in the Viability of Overexpressing Thioredoxin o1 Tobacco BY-2 Cells under Oxidative Conditions

Abstract: Autophagy is an essential process for the degradation of non-useful components, although the mechanism involved in its regulation is less known in plants than in animal systems. Redox regulation of autophagy components is emerging as a possible key mechanism with thioredoxins (TRXs) proposed as involved candidates. In this work, using overexpressing PsTRXo1 tobacco cells (OEX), which present higher viability than non-overexpressing cells after H2O2 treatment, we examine the functional interaction of autophagy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…However, it has recently been reported that overexpression of Pisum sativum mitochondrial thioredoxin (PsTRXo1) in tobacco cells (OEX) showed higher gene expression, higher protein content and higher ATG4 activity than control cells. These and further findings suggest the role of TRXs in mediating the redox regulation of autophagy in plant cells [78].…”
Section: Persulfidated Autophagy‐related Proteins In Arabidopsismentioning
confidence: 95%
“…However, it has recently been reported that overexpression of Pisum sativum mitochondrial thioredoxin (PsTRXo1) in tobacco cells (OEX) showed higher gene expression, higher protein content and higher ATG4 activity than control cells. These and further findings suggest the role of TRXs in mediating the redox regulation of autophagy in plant cells [78].…”
Section: Persulfidated Autophagy‐related Proteins In Arabidopsismentioning
confidence: 95%
“…Proteins were eluted from the columns, after a 5-min pre-incubation at room temperature with 20 μL of elution buffer (50 mM Tris HCl, pH 6.8, 50 mM DTT, 1% SDS, 1 mM EDTA, 0.005% bromophenol blue, 10% glycerol) preheated to 95 °C, by loading four consecutive 50 μL treatments with preheated elution buffer at 95 °C. The eluate was analysed by SDS-PAGE on AnykD gels (Bio-Rad, Spain) and Western blot as previously described [ 30 ]. Polyclonal antibody for PsTRX o 1 was used as described above.…”
Section: Methodsmentioning
confidence: 99%